2010
DOI: 10.2308/jeta.2010.7.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Can Linguistic Predictors Detect Fraudulent Financial Filings?

Abstract: Extensive research has been done on the analytical and empirical examination of financial data in annual reports to detect fraud; however, there is scant research on the analysis of text in annual reports to detect fraud. The basic premise of this research is that there are clues hidden in the text that can be detected to determine the likelihood of fraud. In this research, we examine both the verbal content and the presentation style of the qualitative portion of the annual reports using natural language proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 46 publications
4
86
1
3
Order By: Relevance
“…While financial indicators remain a popular and powerful way to detect fraud, new research has suggested that linguistic analysis of the management discussion and analysis (MD&A) section of 10-K or 10-Q financial statements contains meaningful information to market participants. This type of analysis also has the ability to predict fraud (Cecchini et al 2010a;Glancy and Yadav 2011;Goel and Gangolly 2012;Goel et al 2010;Humpherys et al 2011). There is also meaningful information in news coverage about firms (Tetlock et al 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…While financial indicators remain a popular and powerful way to detect fraud, new research has suggested that linguistic analysis of the management discussion and analysis (MD&A) section of 10-K or 10-Q financial statements contains meaningful information to market participants. This type of analysis also has the ability to predict fraud (Cecchini et al 2010a;Glancy and Yadav 2011;Goel and Gangolly 2012;Goel et al 2010;Humpherys et al 2011). There is also meaningful information in news coverage about firms (Tetlock et al 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior work in this area of fraud detection has explored the language of financial statements (Cecchini et al 2010a;Goel and Gangolly 2012;Goel et al 2010;Humpherys et al 2011) and the verbal (Larcker and Zakolyukina 2012) and non-verbal (Hobson et al 2012;Mayew and Venkatachalam 2012) behavior of executives in the conference calls. This paper is interested in integrating these two data sources to uncover instances of financial fraud.…”
Section: Introductionmentioning
confidence: 99%
“…The deceptive messages showed less lexical diversity (Zhou et al, 2004a). In the research of Goel et al (2010), the lexical diversity is one of the predictive features for fraud in 10-K annual reports. Fuller et al (2011) applied the number of words and sentences and lexical diversity in their machine learning model to detect deceptive utterances in the statements of persons of interest.…”
Section: Descriptive Featuresmentioning
confidence: 99%
“…Several mathematical implementations exist that differ in how they learn the characteristics and construct the model. The Naïve Bayes classifier (NB) and Support Vector Machine (SVM) have been proven successful in text classification tasks in several domains (Cecchini et al, 2010;Conway et al, 2009;Glancy and Yadav, 2011;Goel et al, 2010;He and Veldkamp, 2012;Joachims, 1998;Manning and Schütze, 1999;Metsis et al, 2006;Purda and Skillicorn, 2015). Therefore, this research uses these two types of machine learning approaches to develop text mining models that can detect indications of fraud in the management discussion and analysis section of annual reports.…”
Section: Machine Learningmentioning
confidence: 99%
See 1 more Smart Citation